Vesícula residual - Coelho,Júlio C. U. (2002)
Our objective is to report three patients with recurrent severe upper abdominal pain secondary to residual gallbladder. All patients had been subjected to cholecystectomy from 1 to 20 years before. The diagnosis was established after several episodes of severe upper abdominal pain by imaging exams: ultrasonography, tomography, or endoscopic retrograde cholangiography. Removal of the residual gallbladder led to complete resolution of symptoms. Partial removal of the gallbladder is a very rare cause of postcholecystectomy symptoms.